The Controversy of Hydatidiform Mole Treatment In Women age ≥ 40 year-old - Gabriella Farah; Julita D.L Nainggolan (Fakultas Kedokteran Universitas Pelita Harapan, 2018)
Background: Hydatidiform mole or commonly known as molar pregnancy is one of the gestational trophoblastic disease (GTD) caused by an abnormal trophoblast proliferation. About 50% of gestational trophoblast neoplasm (GTN) arises from molar pregnancy. Higher risk of GTN was found in older patient, especially women age ≥40 years old. Management of hydatidiform mole is often faced come challenges, especially in developing country like Indonesia. Although, suction curettage is the most recommended treatment for the evacuation of molar pregnancy, hysterectomy is considerable for women who have completed childbirth and do not wish to preserve their fertility.Case: Here we present case of 48 years old women with hydatidiform mole. Considering the age of the patient and the completion of her childbearing, we decided to do a laparotomy total abdominal hysterectomy for the evacuation of the mole instead of suction curettage. Turned out that this patient had an invasive mole, one of the types of gestational trophoblastic neoplasia.Conclusion: Although suction curettage is the most frequent technique for molar evacuation, hysterectomy is a reasonable option as primary treatment to be performed in older patients and for those who do not wish to preserve their fertility. The other important points such as socio-economic status, education level, and geographical issues should be considered also on managing older patients with hydatidiform mole in developing countries